Rancang-Bangun Prototipe Sistem Kontrol Berbasis Programmable Logic Controller untuk Pengoperasian Miniatur Penyortiran Material - Arief Goeritno; Surya Pratama (Jurnal Rekayasa Elektrika, 2020)
A miniature sorting of material quality has been made, aided by a prototype of the controller system based on the Mitsubishi FX1N-24MR Programmable Logic Controller (PLC). A number of stages include the manufacture of the conveyor system unit, the electrical system, PLC programming, and performance measurement. The conveyor unit assembling was processed by installing the conveyor belt, dc motor, pneumatic cylinder, solenoid valve, and sensors. The electrical system is an integration of the Mitsubishi FX1N-24MR PLC, switched-mode power supply, miniature circuit breaker (MCB), dc voltage regulator circuit, relays, digital counters, pushbuttons, and selector switches arranged in a 20 x 30 x 15 cm panel box. Mitsubishi PLC system programming is based on algorithmic determination and ladder diagram arrangement assisted by GX Developer (GX Work). Performance measurement in the form of pulse readings is carried out by setting and manufacturing ladder counters and shift registers to count the number of pulses for each material and the accuracy of sorting when the material is detected simultaneously. The system performance is indicated by pulse reading accuracy and sorting timing accuracy. The reading of the pulse from the proximity switch affects the counter calculation to activate the pneumatic cylinder unit in sorting. Sorting for material-A takes 11 pulses, while for material-B, it takes 19 pulses. The synchronization measurement functions when an error occurs in the system in order to maintain the input received is the same as the output in the PLC-based control system.